Philosophical and Religious Justification of Prophecy: A Comparative Analysis Between al-Ghazālī and Maimonides’ Accounts of Prophecy - Widigdo, Mohammad Syifa Amin (Afkar: Jurnal Akidah dan Pemikiran Islam, 2020)
This study examines ideas of two scholars from a different philosophical and religious background. Each of them attempts to provide philosophical and religious justifications for the possibility of prophecy. Abu Hāmid al-Ghazālī (d. 1111) views the notion of prophecy from the Islamic philosophical perspective while Maimonides (d. 1204) discusses it from the Jewish tradition. Modern philosophical and religious studies on the concept of prophecy tend to establish supremacy of certain religious tradition over others. This article presents a comparative account of religious and philosophical contexts in which such tendency of superiority occurs, at the same time, a shared basis of mutual understanding exists. While al-Ghazālī and Maimonides have disagreements on who has the right of the office of prophecy based on the interpretation of their respective religious scriptures, they have an agreement regarding the capacity of human beings in reaching the prophethood. Both employ a philosophical justification to arrive at the conclusion stating that human beings can reach the office of prophecy by using their rational and imaginative faculty. This philosophical exploration and confidence on human reason are both interesting and important for building a solid foundation of respectful dialogue and mutual understanding.